PENGEMBANGAN METODE ANALISIS KINERJA SIMPANG-T TAK-BERSINYAL - Haryadi, Bambang; Narendra, Alfa; Budiwirawan, Agung (FSTPT Indonesia, 2015)
Road capacity guidelines of the developed countries can not be applied with success in Indonesia. Because, that guidelines are generally developed based on homogeneous traffic mainly consists of four-wheeled vehicles, so the presence of motorcycles can be ignored. In addition, traffic behavior patterns in Indonesia is different from that of the developed world. For Indonesian case, guidelines which ignores the existence of motorcycle is clearly unappropriate, because the road traffic is dominated by motorcycles. The purpose of the study was to better understand the actual Indonesian traffic characteristics and driver behavior by taking into account heterogeneous traffic conditions. To achieve the objectives, models were developed for speed, capacity and delay at unsignalized T-intersections using streams of conflicting traffic as predictor. Analysis was done using regression techniques. The study produced speed models, aproach capacity models, and delay models for unsignalized T-intersection as a function of traffic flow. The models can be used as tools for performance analysis of unsignalized T-intersection.